Strengthening Virtual-Based Teacher Protection Insights - Susanto, Susanto (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2025)
This community service activity aims to enhance the knowledge of educators and education personnel regarding teacher protection using an empowerment-based approach. The activity is conducted in three stages: Preparation, Implementation, and Evaluation. In the preparation stage, the researcher identifies issues and intervention needs based on input from teacher respondents, collects data on teacher victimization cases, schedules activities, and designs webinar promotional materials. The implementation stage involves delivering webinar sessions, including material presentations and interactive discussions. At the end of the session, participants provide feedback through an instrument to assess the webinar and suggest improvements. The evaluation stage focuses on the implementation process and participants' comprehension of the material. The results indicate that 98% of participants positively evaluated the webinar process, 95% rated the material clarity highly, 85% expressed satisfaction with the resource persons' responses and committee services, and 95% reported improved insight into teacher protection issues.